The interplay of entrepreneurial and non-entrepreneurial internationalization: an illustrative case of an Italian SME - Nummela Niina; Vissak Tiia; Francioni Barbara (Springer, 2022)
This study describes SME internationalization as a process that combines entrepreneurial and non-entrepreneurial behaviour. We bring in insights from prior literature and use an illustrative case study of an Italian SME to demonstrate the interplay of entrepreneurial and non-entrepreneurial behaviour during the internationalization process. Our study shows that the combination of entrepreneurial and non-entrepreneurial internationalization cannot be fully explained with existing International Entrepreneurship literature or other internationalization theories, as they do not take into account the nonlinear nature of internationalization or explain why the process seems to reach a ‘glass ceiling’ beyond which it does not progress. The study concludes with a conceptual framework providing an alternative explanation. Based on our conceptual reasoning we propose that predominantly non-entrepreneurial internationalization can occur without developing a clearly defined internationalization strategy. Additionally, we argue that low commitment to internationalization prevents capability development and may lead to nonlinear internationalization. Furthermore, we suggest that family involvement may moderate a firm’s international entrepreneurial orientation, consequently leading to more non-entrepreneurial internationalization.